2016
DOI: 10.1007/s00586-016-4564-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the prevalence and characteristics of cervical malalignment in adults presenting with thoracolumbar spine deformity based on variations in treatment approach over 2 years

Abstract: In the first study to compare cervical malalignment at extended follow-up between ASD treatments, CD rates rose overall through 2 years. TLD surgery, resulting in higher CD rates characterized by T1S-CL and cSVA malalignment, produced poorer HRQoL. This information can aid in treatment method decision-making when cervical deformity is present concomitant with TLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…Incidence of prolonged neck pain after spinal surgery has been well described in previous studies, in which it was evident from the lower scores of patient-reported health-related quality of life (HRQOL) parameters [13, 39]. This makes it important to undertake further investigations to develop an understanding of the patho-mechanism of this post-operative cervical pain, with the goal of devising therapeutic or preventative strategies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Incidence of prolonged neck pain after spinal surgery has been well described in previous studies, in which it was evident from the lower scores of patient-reported health-related quality of life (HRQOL) parameters [13, 39]. This makes it important to undertake further investigations to develop an understanding of the patho-mechanism of this post-operative cervical pain, with the goal of devising therapeutic or preventative strategies.…”
Section: Discussionmentioning
confidence: 97%
“…The known global pathologic effects of scoliosis include a deforming coronal deviation of the spine with a concomitant rotation of vertebrae and a flattening of the sagittal profile [11, 12]. In recent studies of adult patients, it has been shown that sagittal alignment has a strong correlation with health-related quality of life scores [13]. Consequently, surgical planning for AIS patients has adopted a focus on sagittal alignment as an important parameter from adult spinal deformity research.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported that TK had a negative correlation with C0–C7 kyphosis and no relationship with C2–C7 kyphosis [29]. In addition, the negative relationship between CK and TK was observed in patients with AIS in several previous publications [2, 18, 24, 25]. Further studies should deeply investigate the effect of TK on CK in asymptomatic populations.…”
Section: Discussionmentioning
confidence: 98%
“…AIS was a three-dimensional deformity of the spine that includes a coronal curve, vertebral rotation, and flattening of the sagittal profile [20–23]. Many studies have demonstrated that some abnormal parameters, such as TK and SVA increased the onset of CK in patients with AIS [5, 18, 24, 25]. Therefore, we hypothesized that these parameters could be related to CK in asymptomatic populations.…”
Section: Discussionmentioning
confidence: 99%
“…25 After correction of the TLD, patients tend to be more misaligned 2 years from surgery with worse TK, T1 slope-cervical lordosis, cervical lordosis, cSVA, C2-T3 SVA, and global SVA compared with patients with TLD who were not operated on. 28 These patients additionally have worse Oswestry Disability Index and Scoliosis Research Society activity at 1 and 2 years. Even after controlling for magnitude of TLD, cervical alignment has a direct effect on health measures.…”
Section: Cervical-thoracic-lumbar Relationshipmentioning
confidence: 96%